The origin of the phrase comparative psychology: an historical overview - d’Isa, Raffaele; Abramson, Charles I. (Frontiers in Psychology, 2023)
Comparative psychology, in its narrow meaning, refers to the study of the similarities and differences in the psychology and behavior of different species. In a broader meaning, it includes comparisons between different biological and socio-cultural groups, such as species, sexes, developmental stages, ages, and ethnicities. This broader meaning originated by extension from the former narrow meaning, which historically was the original meaning of the phrase (interspecies psychological and behavioral comparisons) and which still today is the focus of the field. Currently, comparative psychology is a subject of study in hundreds of universities all over the world. Nevertheless, a question that is often asked but seldom answered is: when did the phrase comparative psychology first appear and where did it come from? In the present work, we tracked down the origins of the phrase comparative psychology. In order to do so, at first we described the origin of the word psychology, coined in the decade 1510–1520 in the Republic of Venice by Dalmatian Renaissance humanist Marko Marulić Splićanin (1450–1524). Then, to explain where, within the phrase comparative psychology, the term comparative came from, we outlined the origin of the use of the word comparative in reference to interspecies comparisons. Finally, we reported the origin of the combination of the words comparative and psychology to form the phrase comparative psychology, the first usage of which was in 1778 by German scholar Michael Hissmann (1752–1784) from the University of Göttingen. Origins of the phrase in Latin, German, French and English languages are described.